Optimalisasi Pendataan Cuti Kepegawaian Di Kantor Wilayah Direktorat Jenderal Perbendaharaan Provinsi Sumatera Utara - Nadinda Tefa; Kusmilawaty Kusmilawaty (BADAN PENERBIT STIEPARI PRESS, 2024)
Leave is an employee's right not to work for a certain period of time for reasons of personal or family interests. Optimal leave management can help organizations maintain employee work productivity and ensure that employee leave needs are met. This research aims to analyze the optimization of employee leave data collection at the North Sumatra DJPB Regional Office which is still not optimal due to the organization of leave data which is still not regular and systematic. This research uses a qualitative approach with a case study method and research data obtained through interviews, observation and document study. Based on the results of research that has been carried out, it can be concluded that data collection on employee leave at the Regional Office of the Directorate General of Treasury of North Sumatra Province is still not optimal. This is caused by the arrangement of leave data which is still random and not regular. Apart from that, irregular data arrangement also hinders the optimization of employees' work. Therefore, to make data collection on employee leave more effective, the author reconstructed the data collection on employee leave at the Regional Office of the Directorate General of Treasury of North Sumatra Province.